(untitled) (Latakia University Journal -Basic Sciences Series, 2020)
A series of samples of the piezoelectric compositions with calcined at temperature of for have been synthesized by the solid-solutions method. The compositions are crystallized as structure under the preparation conditions. The structural changes and thermal stability as a function of the ratio were investigated by using X-ray powder diffraction XRD and differential thermal analysis DTA. The study of XRD spectrum showed that the solid solution formation between FePO4 and AlPO4, takes place by incorporation of Fe3+ ions into the AlPO4 structure. This solid solution formation is accompanied with a phase transformation to phase at the temperatures (920 – 940) for the ratios respectively. The changes in the chemical bondslengths and their effects on the structure of these compositions were studied using different methods of spectral analysis; the spectra of , , and as a function of . Thermal stability and phase transition temperature of the two samples prepared has been found to be higher for the ratios than for each of the and .